Téma dopisu v naivní poezii dospívajících dívek - Bittnerová, Dana (Lidé města, 1999)
The life of children within the framework of the culture of adult people in the 20th century has been influenced by the adoption of a number of cultural phenomena and it has brought about the widening of formal as well as content parts of the folklore. As a result, the children's literary tradltion includes not only literary forms which are conveyed verbally. Small literary works of scriptural culture are of the same validity and importance. All phenomena currently regarded as part of children's scriptural culture have their model in the culture of adult people. Those with the most stable content, form and function include, along with momente books and handwritten songbooks, also notebooks with quotations, naive poetry, short forms of humorous and amorous prose, and tests. They have mainly become the ownership of girls. The notebooks were established at the age of puberty, at the time of search for one's own attitude to love, friendship and the world. When selecting the texts the girls' notebooks maintained partial continuity with its predecessors - notebooks with quotations - anď they were based on them. Books and magazines became another source (again quotations, strophes of songs, naive poetry and tests). The text parts of notebooks included to a large extent paraphrases of authorship creations, their own texts as well as adopted naive poetry and prosaic work which were present in verbal or literary tradition. It is a question when this elemenl of children's culture came into being. Anyway, in the 1970s the notebooks of quotations, naive poetry, prosaic work and tests were already subject to tradition. They were copied, although they remaíned open to borrowed literary forms. The owners of notebooks, too, often used the collected texts as a pattern in another cultural element (such as text in a momento book, a love letter, etc.) or in another context (tests were, e.g., used in games). Girls' handwritten books have included naive poetry - short verses in letters, greetings and congratulations. Similarly to other texts in notebooks, these verses, too, constituted not only another gained "item" for the collectlon of texts, the girl liked, but they could also be used in correspondence. Sometimes they only existed in correspondence, witbout the support of the notebook. The presented verses are extractions from my collections from the early 1990 from the girls living in Prague and Vlašim. They were sorted into a selection which depicts the texts bound to the address, beginning of a letter, end of a letter, greetings and congratulations as well as letters written directly on thee envelope of a letter. The selection does not correspond with the authentic order or structure of texts of notebooks.